BIMBINGAN TEKNIS PERENCANAAN MENARA MASJID RADEN RAHMAD MERJOSARI LOWOKWARU KOTA MALANG - Moch. Khamim; Winda Harsanti; Mohamad Zenurianto (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
The minarets are a distinctive traditional feature of many mosques, although they vary in height, style, and number. Towers can be square, round, hexagonal, octagonal, or even spiral and towers are usually covered with a gabled roof. Mosque minarets Generally a tall minaret with a cone or onion-shaped crown, usually standing alone or higher than the surrounding structures. The basic form of the tower includes a base, shaft, and gallery. The style varies according to region and time period. The minaret provides a visual focal point and is traditionally used for the Muslim call to prayer (Azan). A good tower must be designed according to the shape of the mosque and the structural needs are calculated.